Race, Immigration, and Social Control Immigrants' Views on the Police - Sun, Ivan Y. (Palgrave Studies in Race, Ethnicity, Indigeneity and Criminal Justice, 2018)
This book discusses the issues surrounding race, ethnicity, and immigrant status in U.S. policing, with a special focus on immigrant groups' perceptions of the police and factors that shape their attitudes toward the police. It focuses on the perceptions of three rapidly growing yet understudied ethnic groups - Hispanic/Latino, Chinese, and Arab Americans. Discussion of their perceptions of and experience with the police revolves around several central themes, including theoretical frameworks, historical developments, contemporary perceptions, and emerging challenges. This book appeals to those interested in or researching policing, race relations, and immigration in society, and to domestic and foreign government officials who carry law enforcement responsibilities and deal with citizens and immigrants in particular. .